Demystifying Renal Tubular Disorders in children : A simplified approach - Shobha, Sharma; Suprita , Kalra (Indian Journal of Child Health, 2024)
Renal tubular disorders essentially include all disorders of the highly specialized channels of the renal tubular system, from the proximal convoluted tubule to the cortical and medullary collecting ducts. This tubular system is responsible for reabsorption of 99% of glomerular ultrafiltrate, which contains a large amount of fluid (approximately 180 L/day) as well as most electrolytes and many metabolites such as glucose (G), amino acids, bicarbonate (HCO3-), phosphate (PO4 3-), and low-molecular-weight proteins and is essential for maintaining fluid, electrolyte, and acid–base balance. In this review, we will briefly discuss when to suspect a renal tubular disorder, a simplified algorithm for evaluation, and specific mutations of a few common disorders.